Developing Decision Model by Mining Historical Prices Data of Infosys for Stock Market Prediction - Gour, Sanjeev (International Journal of Computer Sciences and Engineering, 2025)
Stock market analysis is the process of analyzing and monitoring stocks so it is also a process of calculating the future trends on the basis of historical trends. This whole concept is volatile, as the stock prices having the tendency to rise and fall. However, we know that there is a defined pattern in insight of any sequenced event therefore we can extract some hidden pattern thorough analysis. In this paper we have developed a decision support model to classify and predict the stock market by data mining techniques like classification and prediction. In this way we have developed some decision rules as model to increase the probability of right decision so that an investor can took profit in the stock investment. in this study we analyze the historical price data of the specific industry group Named Infosys Pvt. Ltd. to make sure that the investors is moving with right decision in order to increase the possibility of profit in their investments. Therefore the main task is to predict and classify the stock prices of Infosys Company on the basis of past prices.